Nutritional stimuli of gilthead seabream (Sparus aurata) larvae by dietary fatty acids: effects on larval performance, gene expression and neurogenesis. (27th August 2015) - Turkmen, Serhat; Castro, Pedro Luis; Caballero, María José; Hernández‐Cruz, Carmen María; Saleh, Reda; Zamorano, Maria Jesus; Regidor, José; Izquierdo, Marisol
Abstract: The concept of nutritional programming raises the interesting possibility of directing specific metabolic pathways or functions in juvenile fish, for example, to improve the use of substitutes to fishmeal and oil, and hence to promote sustainability in aquaculture. The aim of the study was to determine effects of early nutritional stimuli of gilthead seabream larvae and check if nutritional programming of gilthead sea bream is possible between 16 days post hatching (dph) and 26 dph. A trial was conducted to determine the effects of early nutritional stimuli of gilthead seabream larvae. Five experimental microdiets (pellet size <250 μm) were formulated containing five different proportions of a marine lipid source rich in long‐chain polyunsaturated fatty acids (LC‐PUFA) and two vegetable lipid sources rich in linolenic and linoleic acids. The results of this study demonstrate that dietary n‐3 LC‐PUFA levels increased larval growth and survival affecting Δ6 desaturase gen ( fads2 ) expression and retinal neurons density. However, the high mortalities obtained along on‐growing in fish fed low n‐3 LC‐PUFA at 16 dph constrained the feasibility of nutritional programming of gilthead seabream during this late developmental window and needs to be further investigated.